Popcorn Capsulorrhaphy in Revision Aesthetic Breast Surgery. (13th December 2018) - Calobrace, M Bradley; Mays, Chet; Wilson, Ryan; Wermeling, Ryan
Abstract: Background: Control of the pocket in revisional breast surgery can be technically challenging and unpredictable. A capsulorrhaphy technique has been utilized in altering capsules in secondary aesthetic breast surgery. Objectives: The authors sought to determine the effectiveness of popcorn capsulorrhaphy in revisional breast surgery. Methods: A retrospective chart review of revisional breast cases utilizing popcorn capsulorrhaphy was conducted between September 2015 and August 2017. Only aesthetic breast cases were included. Data were collected for 149 patients. Results: One hundred forty-nine patients representing 266 breasts were operated on. The average patient age was 42 years and the mean body mass index was 24.2 kg/m 2 . The average time from their original surgery to the popcorn capsulorrhaphy secondary procedure was 9.3 years. Indications for capsulorrhaphy included malposition in 163 breasts (61.3%), implant positioning for breast ptosis in 34 breasts (12.8%), pocket adjustment for implant size change in 49 breasts (18.4%), and postexplantation pocket reduction in 20 breasts (7.5%). Of the 266 implants, 145 (54.5%) were smooth, 101 (38%) textured, and 20 (7.5%) were explanted. The average original implant size was 405 cc and the average size placed at the time of capsulorrhaphy was 422 cc. Two hundred thirty-six (88.7%) were in a submuscular pocket and 30 (11.3%) were subglandular. The total number of complications was 39 (14.7%), and 16 (6%) required some type of operative revision. Conclusions: Popcorn capsulorrhaphy can provide pocket control and stability with low complication and revision rates. The addition of a mesh or biologic at the time of popcorn capsulorrhaphy can further lower the complication and revision rates. Level of Evidence: 4: